Analisis Pengaruh ROA, ROE dan DER terhadap Harga Saham Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia - Nengsih, Titin Agustin; Sartika, Yusi; Romeo, M.Yusuf (Jurnal Accounting Information System (AIMS), 2024)
The purpose of this study is to find out the extent of the influence of ROA, ROE, DER on the stock price of financial companies on the IDX for the 2021-2023 period. This application uses quantitative delinquency with descriptive and causal statistics, with the type of data that is included from the report of the leisure company registered in BEI. The data analysis technique used in this pelnellitian is linear relgrelation analysis. The results of the analysis show that Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER) have a significant effect on the stock prices of financial companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. ROA and ROE show a positive relationship with stock prices, meaning that the efficiency of asset use and returns to shareholders contribute to the increase in stock prices. On the other hand, DER has a negative correlation with stock prices, suggesting that increased leverage of companies tends to lower the stock market value due to higher financial risks. The panel data regression models, both Fixed Effects (FE) and Random Effects (RE), show consistency in the finding that company profitability measured through ROA and ROE increases the stock price, while high leverage measured through DER decreases the stock price. The Chow and Hausman tests also support that the FE model is better suited to analyze this data, suggesting significant structural differences between companies.